2009
DOI: 10.1021/om801080p
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Highly Active Ruthenium(II) NNN Complex Catalysts Bearing a Pyridyl-Supported Pyrazolyl-Imidazolyl Ligand for Transfer Hydrogenation of Ketones

Abstract: A family of hemilabile ruthenium(II) NNN complexes bearing a unsymmetrical 2-(benzoimidazol-2-yl)-6-(pyrazol-1-yl)pyridine ligand has been synthesized and exhibited good to excellent catalytic activity in transfer hydrogenation of ketones in refluxing 2-propanol, reaching final TOFs up to 7.2 × 105 h−1 with 0.05 mol % loading. The γ-NH effect of the benzoimidazol-2-yl moiety in the ligand and coordination modes of the metal center in a Ru(II) NNN complex has great influence on the catalytic activity of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 55 publications
1
40
0
Order By: Relevance
“…As the bulkiness of the substituents decreased from bromo to chloro, the resultant enantioselectivity decreased from 95% to 93% (entries 4 and 5, Table 3). We have previously shown that a benzimidazolyl N-H in a ligand can accelerate the TH and ATH of ketones [28][29][30], and an imidazolinyl N-H functionality has also been reported as improving the enantioselectivity in ATH [38]. In our case, the combination of the two N-H functionalities may provide the complex catalysts with high catalytic activity and good selectivity for ATH of ketones under mild conditions.…”
Section: Asymmetric Transfer Hydrogenation Of Ketonesmentioning
confidence: 60%
See 2 more Smart Citations
“…As the bulkiness of the substituents decreased from bromo to chloro, the resultant enantioselectivity decreased from 95% to 93% (entries 4 and 5, Table 3). We have previously shown that a benzimidazolyl N-H in a ligand can accelerate the TH and ATH of ketones [28][29][30], and an imidazolinyl N-H functionality has also been reported as improving the enantioselectivity in ATH [38]. In our case, the combination of the two N-H functionalities may provide the complex catalysts with high catalytic activity and good selectivity for ATH of ketones under mild conditions.…”
Section: Asymmetric Transfer Hydrogenation Of Ketonesmentioning
confidence: 60%
“…Following the procedure previously reported from our laboratory [21][22][23][24][25][26][27][28][29][30][31][32], complex 6a was tested as a catalyst for the transfer hydrogenation of acetophenone in the presence of i-PrOK. To our surprise, 6a exhibited excellent catalytic activity for the reduction of acetophenone in 2-propanol even at room temperature (28 °C).…”
Section: Transfer Hydrogenation Of Ketonesmentioning
confidence: 99%
See 1 more Smart Citation
“…[42] Notably, the related imidazole complex 34 bearing an NH group at a more remote g-position exhibits much higher catalytic activity. [43] This observation implies indirect participation of the b-protic group to the catalysis; the deprotonation may just increase the lability of the halide ligand to produce a vacant coordination site. The proposed mechanism of the transfer hydrogenation thus involves conventional b-elimination and migratory insertion steps without cooperation of the uncoordinated nitrogen atom and is not truly bifunctional.…”
Section: Protic Pyrazole Complexesmentioning
confidence: 99%
“…Compared with the commonly used reduction processes which involve high hydrogen pressure or hazardous reducing reagents [2][3][4], transfer hydrogenation has emerged as a safe, ecofriendly and versatile tool for the reduction of carbonyl compounds. Recently, the Ru(II) complexes bearing planar tridentate N 3 ligands and unsymmetrical planar tridentate ligands have been successfully developed and explored to construct the effective catalyst systems for the transfer hydrogenation of ketones [5][6][7][8][9][10]. In the study of the transfer hydrogenation mechanism, several ruthenium hydride complexes are considered as active species [11][12][13][14][15][16][17][18], but some ruthenium hydride complexes, such as RuHCl(PPh 3 ) 3 [11], are not the really active species.…”
mentioning
confidence: 99%